Diarrhoea associated with medullary carcinoma of the thyroid. Issue 12 (December 1969) - Bernier, J. J.; Rambaud, J. C.; Cattan, D.; Prost, A.
Abstract : Diarrhoea, which is present in roughly one third of cases of medullary carcinoma of the thyroid, was investigated in five cases. Excessive loss of water and electrolytes in the stools was the major factor. Steatorrhoea was mild or absent, and intestinal absorption of glucose and vitamin B12 was normal; the histological appearance of the small intestinal mucosa was normal or subnormal. Water and sodium diarrhoea seems to be linked to a sometimes considerable increase in the rate of transit through the small intestine and colon, and may be relieved by codeine or codethyline. The frequent increase in the maximum blood sugar level during an oral tolerance test should not be interpreted as evidence of a paradiabetic condition. In fact, the intravenous glucose tolerance test is usually normal and the excessive rise in blood sugar after oral administration seems to be the consequence of the increased rate of transit through the small intestine. The link between the tumour and the disordered motility seems definite in view of certain cases in which removal of the tumour caused the diarrhoea to disappear immediately. Production by the tumour of serotonin or other derivatives of tryptophan or of kallikrein, which activates bradykinin, is rare. With regard to prostaglandins, high concentrations have been observed in the tumours and in the venous blood draining the tumours, but their presence in systemic blood is inconstant. The only hormonal substance, concentration of which seems to be definitely increased in the systemic blood of patients with a medullary carcinoma of the thyroid, is thyrocalcitonin but this hormone does not seem to have any effect on the motor activity of the digestive tract.